Ruga Settlement Initiative: A Panacea for Conflict Between Herdsmen and Farmers in Nigeria. - Abdullahi, Shehu, Abdulkadir (My University, 2023)
Recent killings and destruction of lives and property by a particular tribe known as the Fulani have been in the spotlight for some time. Their actions against the farmers have rendered so many homeless and incapacitated. This situation is appalling, as every passing day brings in fresh news about the destruction carried out by the group. This necessitated the ruga program, aimed to address issues related to livestock management promote agriculture and reduced conflict between farmers and headers. The federal government of Nigeria believed, it will drastically reduce conflict between the farmers and the herdsmen and in extension become economically beneficial. This study adopted the critical analysis method and the findings revealed that the ruga program though with its benefits will not survive due to widespread criticism and disagreement. The perceived benefit varied depending on different perspectives but overall, the intent was to modernized livestock farming practices and enhanced food security.
Keywords: Farmers; Fulani; Hausa; Headers; Ruga